2018
DOI: 10.1016/j.pharep.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-mediated induction of S-phase cell cycle arrest and apoptosis in COLO829 melanoma cells

Abstract: The obtained results for COLO829 melanoma cells were compared with data for normal dark pigmented melanocytes and the use of ciprofloxacin as a potential anticancer drug for the treatment of melanoma in vivo was considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…The highest concentration of ciprofloxacin (1.0 mM) induced oligonucleosomal DNA fragmentation (the presence of sub-G 1 fraction), strongly suggesting that apoptosis was induced via the p53-dependent pathway. These results are consistent with the results of our recent study, which revealed that ciprofloxacin mediates the induction of S-phase arrest and apoptosis in COLO829 melanoma cells (41). They are also consistent with the results of study by Yadav et al (13), which identified the ability of ciprofloxacin to induce DNA fragmentation and S-phase arrest in human pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…The highest concentration of ciprofloxacin (1.0 mM) induced oligonucleosomal DNA fragmentation (the presence of sub-G 1 fraction), strongly suggesting that apoptosis was induced via the p53-dependent pathway. These results are consistent with the results of our recent study, which revealed that ciprofloxacin mediates the induction of S-phase arrest and apoptosis in COLO829 melanoma cells (41). They are also consistent with the results of study by Yadav et al (13), which identified the ability of ciprofloxacin to induce DNA fragmentation and S-phase arrest in human pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…The anticancer activity of Ciprofloxacin has been demonstrated in human and animal cancer cell lines in vitro, such as human bladder cancer cell lines, human colorectal cell lines, hamster ovarian cancer cell lines, and human hepatocellular carcinoma [33,34]. Artur Beberok and Dorota Wrzesniok et al have shown that the incubation period would be extended to 48 h and 72 h in low concentration (0.01 mM and 0.1 mM) of ciprofloxacin, and that melanoma cells would appear stagnation of S phase of the cycle by cell fluorescence image analysis through mechanisms associated with topoisomerase II inhibition [33,34]. In contrast, Kloskowski et al demonstrated that ciprofloxacin caused cell stagnation at the G2/M checkpoint in human non-small cell lung cancer [35].…”
Section: Ciprofloxacinmentioning
confidence: 99%
“…Cell cycle phase distribution of astrocytes after the 27 day culture in medium with/without (OH)Cbl(c-lactam) was analyzed following a previously described method [21]. In brief, cells were fixed with ice-cold 70% ethanol at 4 • C for 24 h, stained with Solution 3 for 5 min at 37 • C, and then analyzed using the image cytometer with the adequate protocol-Cell Cycle Analysis of Fixed Cells or DNA Fragmentation Assay (ChemoMetec).…”
Section: Cell Cycle Assay and Dna Fragmentation Assaymentioning
confidence: 99%
“…Astrocytes at day 27 of culture with/without (OH)Cbl(c-lactam) were examined in terms of the mitochondrial transmembrane potential (∆Ψ m ). The analysis was performed using the image cytometer NucleoCounter NC-3000 following JC-1/DAPI staining according to a previously described method [21].…”
Section: Mitochondrial Potential Assaymentioning
confidence: 99%